Non-aromatic Si, P, N-containing hyperbranched flame retardant on reducing fire hazards of epoxy resin with desirable mechanical properties and lower curing temperature. (1st October 2021) - Zhang, Yuanbo; Yan, Hongxia; Feng, Guangpeng; Liu, Rui; Yang, Kaiming; Feng, Weixu; Zhang, Shuyi; He, Chuang
Abstract: Plastic combustion has adverse impacts on air quality and human health. In this work, a novel non-aromatic Si, P, N-containing hyperbranched flame retardant (HPNSi ) was synthesized and proposed to epoxy resin. The modified epoxy exhibits not only reduced fire hazards and less smoke production in favor of eco-friendly, but also remarkable mechanical properties and lower curing temperature for facile processability. With 6 wt% incorporation, the peak heat release and total smoke production were reduced by 29.6% and 20.7%, respectively, and the time to ignition (TTI) increased as well as the fire growth rate (FIGRA) dropped off, which is of vital significance for saving lives in a fire. Meanwhile, the impact strength and flexural strength greatly enhanced by 72.9% and 22.0%, while its curing temperature was lower than that of controlled EP system. Interestingly, we also found that the solid carbon particles on the char surface apparently reduced from SEM image. The blending of its unique non-aromatic hyperbranched structure containing Si, P, N with epoxy architecture was responsible for the desirable integrated enhancement. The broad possibilities in the field of flame-retardant plastic with reduced fire hazards and excellent integrated performance enable the novel hyperbranched flame retardant a bright future for application. Graphical abstract: Image 1 Research Highlights: Non-aromatic Si, P, N-hyperbranched FR was synthesized by facile polycondensation. Significantly enhanced flame retardancy and low smoke release were achieved. The HPNSi/EP exhibits outstanding mechanical properties and rapid curing rate. Phosphorus group introduce to hyperbranched architecture led to great enhancement. SEM show that HPNSi may inhibit carbon particle release on the char surface.